A multi-parameter data-assimilation approach for wave prediction in coastal areas. Issue 1 (2nd January 2016) - Rusu, Eugen; Raileanu, Alina
ABSTRACT: This work describes an approach based on the successive correction method for assimilating in situ measurements in the high-resolution computational domain of a wave-modelling system based on the spectrum concept. Its objective is to improve the wave predictions in the nearshore and in the vicinity of the harbours. The coastal environment targeted is the western side of the Black Sea, but similar approaches can be developed for any nearshore area where in situ wave measurements are available. A wave modelling system based on the simulating waves nearshore (SWAN) model was implemented for the entire sea basin. On the western side, a higher-resolution computational domain was nested in the large area. Wave measurements from the Gloria drilling unit were considered for the assimilation procedure. For several boundary points of the last computational domain, corrections of the main wave parameters were performed which take into account the measured values. In this case, only the significant wave height and peak period were assimilated, but the wave direction and the directional spreading can be also assimilated as a further computational step. Considering these corrected values, parametric boundary conditions are used to force the model. As a result, the wave-prediction system becomes more reliable.